2022
DOI: 10.1002/ccr3.6263
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Paget's disease with bilevel cord compression and ischemic non‐compressive myelopathy treated with zoledronic acid

Abstract: Cord compression and ischemic non‐compressive myelopathy are a complication of spinal Paget's disease (SPD). SPD usually touches a single spine level. We report an unusual case with bilevel spinal cord compression and dysfunction which was medically treated due to resolution of the vascular steal syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Multiple examples of the effectiveness of medical therapy are documented. 7 Feki et al 13 reported a 62-year-old patient with both thoracic and lumbar spinal cord compression secondary to PDB, treated with an intravenous infusion of 5 mg of zoledronic acid without surgical intervention. The patient saw a decrease in ALP as well as objective improvements in power and sensory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple examples of the effectiveness of medical therapy are documented. 7 Feki et al 13 reported a 62-year-old patient with both thoracic and lumbar spinal cord compression secondary to PDB, treated with an intravenous infusion of 5 mg of zoledronic acid without surgical intervention. The patient saw a decrease in ALP as well as objective improvements in power and sensory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, diagnosis of PDB is usually a secondary finding on an abnormal X-ray, CT, MRI, or hybrid imaging (positron emission tomography and CT; PET/CT) [5,[25][26][27][28][29][30][31] and/or elevated alkaline phosphatase activity of an unknown etiology, as in our patient [21,24]. The characteristics listed above that lead to the diagnosis are related to earlier and wider access to medical examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The most common PDB involvement sites are the pelvis, lumbar spine, and femur, reported in more than 75% of cases, with the polyostotic disease being more common than the monostotic [13], but the axial skeleton is usually involved. It is assumed that about 75% of patients are asymptomatic [22], although some studies indicate that pain in the affected site is the most common symptom [25][26][27], along with deformity and fracture [22,25]. PDB occurs more often in men than women and is uncommon in people under 50.…”
Section: Discussionmentioning
confidence: 99%